Investigation on the Occurrence of Aedes Species in Borderline of Iran and Azerbaijan for Control of Arboviral Diseases - Eslam Moradi-Asl; Hassan Vatandoost; Davod Adham; Daryosh Emdadi; Hassan Moosa-Kazemi (Tehran University of Medical Sciences, 2018)
Background: To investigate the diversity of the genus Aedes present in the natural areas of Ardabil Province, north-west of Iran. Methods: This cross-sectional study was carried out from Apr to Oct 2016 in North-western of Iran. Thirty-three areas of 10 cities which are border areas were selected randomly. The larvae were collected 2 times in each month during the seasonal activities of mosquitoes and the larvae were identified morphologically according to the appropriate identification keys. Results: Overall, 694 larvae were collected from four counties, from which only 7.2% were Aedes larvae. Three species of Aedes were identified which include Ae. caspius, Ae. vexans and Ae. flavescens. Aedes flavescens is reported from Ardabil Province for the first time. Conclusion: Aedes species were a high density in borderline of Iran and Azerbaijan. Therefore, the north parts of Ardabil Province are a suitable habitat for Aedes species mosquitoes. Care should be taken for vector control in the case of occurrence of any arboviruses transmitted by Aedes mosquitoes.